PEMANFAATAN APLIKASI NETBEANS DALAM PRAKTIKUM PEMROGRAMAN JAVA DI SMK IBRAHIMY 1 SUKOREJO - Zaehol Fatah; Riskiyatul Hasanah (CV. Denasya Smart Publisher, 2026)
Advancements in information technology have significantly influenced the learning process, particularly in the field of computer programming within vocational high schools. NetBeans is a commonly used application for teaching Java-based programming. This study aims to examine the use of NetBeans in Java programming practical sessions at SMK Ibrahimy 1 Sukorejo, identify the benefits of using the software, and determine the obstacles encountered during these sessions. The findings from the community service activity conducted at SMK Ibrahimy 1 Sukorejo indicate that NetBeans facilitates students' understanding of Java programming syntax through features such as a code editor, debugging tools, and an interface that streamlines the program development process. Furthermore, the use of NetBeans enhances the effectiveness of practical sessions by allowing students to quickly execute and test their programs. However, certain challenges were identified, including students' limited understanding of programming logic, syntax errors, and hardware limitations in some instances. Consequently, NetBeans is considered an effective tool for supporting Java programming practical learning in schools.